2002
DOI: 10.21236/ada404806
|View full text |Cite
|
Sign up to set email alerts
|

Navy Speciality Physician Study: Historical Overview, Retention Analysis, and Synopsis of Current Civilian-Sector Practices

Abstract: PGY-2+ d d. PGY-2+ are residents and fellows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Navy physicians also responded to monetary incentives and it appeared that civilian-military pay influenced the retention decision. In a more recent look at Navy physicians, Christensen et al (2002) reported retention trends among HPSP physicians that attended civilian residencies that were similar to those reported by McMahon (1989).…”
Section: Retention Of Military Physicianssupporting
confidence: 72%
“…Navy physicians also responded to monetary incentives and it appeared that civilian-military pay influenced the retention decision. In a more recent look at Navy physicians, Christensen et al (2002) reported retention trends among HPSP physicians that attended civilian residencies that were similar to those reported by McMahon (1989).…”
Section: Retention Of Military Physicianssupporting
confidence: 72%
“…For example, the FY 1991 survival curve plots the percentage of the 7,375 physicians 24. In the private sector, physician turnover in 1999 was about 10 percent [23]. Consequently, we think it might be very difficult for the military to reduce its physician attrition to less than 10 percent.…”
Section: Continuation Ratesmentioning
confidence: 97%
“…This policy changed the involuntary obligation time and continuation of medical corps officers trained in-house [21 ]. As a result of this policy change, recent CNA research [23] showed that, although physician retention for Navy AFHPSP direct accessions was lower before residency training, it was higher after residency training. Next we consider the effects of accession source and specialty group on retention.…”
Section: Basic Cohort Analysesmentioning
confidence: 99%